(Re)articulação do planejamento estratégico e a gestão participativa no contexto escolar - Trindade, Fernando Cunha (2021)
This research is linked to the Professional Master of the Postgraduate Program in Public Policy and Educational Management, from the Federal University of Santa Maria, and it address as theme the Strategic Planning in School Management. It aims to understand the challenges e possibilities related to the (re) articulation of strategic planning as a driver of participative management in the context of a public school in Santa Maria, Rio Grande do Sul. The specific objectives are: a) to identify the administrative and financial dimensions, as well as their incidences on the pedagogical work of a public school managers; b) to recognize the modes of participation of public managers in the school context, regarding teacher training and pedagogical praxis; c) to know how the managing leaders articulate the different actors for the development of the political pedagogical project; d) to identify the levels of participation of school actors in the planning, development e evaluation of school management; e) to propose guidelines of dynamization and (re) articulation of strategic planning to the management team of a public school. Research in education, with a qualitative approach, is characterized as descriptive and interpretative, of the case study type, developed in a State Public School in Santa Maria, RS. Literature review, document analysis, exploratory questionnaire and semi-structure individual interview, proposed by Gaskell (2003), were used. Data were analyzed and triangulated (sources of information) with the support of Discursive Textual Analysis (DTA), by Moraes e Galiazzi (2006). The protagonists were the teachers working on the management team and a representative of the School Council. The theoretical framework in this dissertation involved mainly the studies of Paro (2016) e Lück (2013). In the investigated school, there is an effective integration (horizontality) among the management team, the continuing education of teachers even with the express determinations from the maintainer, the participation of organizations (School Council and Circle of parents and teachers) in the pedagogical, administrative and financial instances, however, it turns out a low participation of the community, employees and even teachers in certain aspects related to management and the PPP. It is expected that the present research, through the guidance of the final product, that configure the SWOT analysis and the organizational construction of strategic planning, can contribute to build qualitative paths of participation of educational managers in the pedagogical spaces of the school, qualifying and legitimizing the strategic school planning necessary to achieve the objectives proposed with the community involved.